L’image visible des grâces invisibles : Rhétorique de l’éloge et stratégies de l’écart dans les sermons funèbres protestants, c. 1600-1640 - Paula Barros (Revue LISA)
Relying on both rhetorical patterns and theological doctrines, preachers in early-modern England redefine the classical theory of funeral eulogy as they rewrite the lives of the deceased to make them conform to the Protestant ideal of godliness. In some cases, however, they manipulate the patterns of praise, inviting their audiences to read between the lines. Thus, they are able to fulfil the obligations imposed on them by the quest for patronage while still providing a fundamentally truthful account of the life of the deceased.